Effects of Microbial Phytase Supplementation on Mineral Composition of Tibia and Mineral Utilization in Broiler Fed Maize - Based Diets - Adebiyi, O.A.; Ologhobo, A.D.; Agboola, A.S. (International Journal of Poultry Science, 2009)
An experiment was conducted to determine effect of supplementing maize - based diet with different levels of microbial phytase on apparent nutrient bioavailability and tibia bone mineral of broilers. Eighty, day-old broiler were randomly allotted to five dietary treatments. The control diet contained 0 FTU/kg microbial phytase which was replaced by 200, 400, 600 and 800 FTU/kg microbial phytase of the basal feed combinations. Phytase supplementation of diet increased P, Ca, Zn, Cu and Phytate - P bioavailability significantly with 800 FTU/kg microbial phytase inclusion. No significant (p>0.05) difference was observed in the calcium content (r = 0.94) of the tibia bone of birds fed diets 400 (38.90%), 600 (38.91%) and 800 (39.08%) FTU/kg microbial phytase. Although, the phosphorus contents of birds fed diets containing 200 FTU/kg, 400 FTU/kg and 600 FTU/kg were not significantly (p>0.05) different, the copper and iron levels were however vary significantly. The result also showed a significant correlation (r = 0.98) between the phytase level and phytate phosphorus.